Remembering Ilya Moiseevich Smolar - Tovmasyan, Eduard (project baikal, 2019)
On April 10, 2018, the Department of urban planning of the Russian Academy of architecture and construction Sciences held a meeting "Remembering Smolar", the sacred 12 February 90th anniversary of the birth of doctor of architecture, Professor, full member of RAACS Ilya Moiseevich Smolar, who left our world 10 years ago. The initiator of the meeting was a student of Ilia Moiseevich, who successfully defended his PhD thesis, now the chief architect of Moscow Institute "Giprogor" Alexander Albertovich Kolesnikov. The program of the meeting provided to recall the scientific, pedagogical and human qualities of I. M. Smolar, as well as the discussion of modern scientific and legal issues of our urban development. The author provides the reader with an opportunity to get acquainted with the content of his speech at this meeting, dedicated to the human qualities of the Master.